The Effect of Stress Management Training on Positive Experiences of Families Caring for Patients with Schizophrenia - Saeed Vaghee; Mahdi Rezaei; Negar Asgharipour; Hamid Chamanzari (Mashhad University of Medical Sciences, 2017)
Background: Living with schizophrenic patients and its associated stress and negative psychological burden can bring about different experiences for their families. The provision of stress management training for these families can be helpful in increasing self-confidence and enhancing interpersonal communication in these caregivers, which can improve their mental health status and enhance the quality of patient care. Aim: Regarding this, the aim of the present study was to investigate the impact of stress management training on positive experiences of the families giving care to patients suffering from schizophrenia. Method: This randomized controlled clinical trial was conducted on 57 primary caregivers of schizophrenic patients admitted to Ibn Sina Hospital in Mashhad, Iran in 2016. For the purpose of the study, the participants were divided into the control (including 29 individuals) and experimental groups (entailing 28 subjects). Subsequently, a stress management training program was administered on the experimental group within six one-hour sessions. On the other hand, the control group only received educational pamphlets on stress management at the end of the study. Additionally, the standardized Experience of Caregiving Inventory developed by Szmukler et al. was filled out by the caregivers before and three months after the intervention. The data analysis was performed using independent-samples t-test and Mann-Whitney U test through SPSS version 11.5. Results: The findings of this study revealed that 50% (14 cases) and 69% (20 subjects) of the participants in the experimental and control groups were female, respectively. The results revealed no significant differences in the total scores for positive experiences of the caregivers in the control (61.2±17.3) and experimental groups (62.3±20.7) at the pre-intervention stage (P=0.40). Likewise, no significant difference was observed between the total scores of the control group (64.5±14.3) and experimental group (67.6±12.9) at the post-intervention stage (P=0.40). Conclusion: Given the findings of the present study and considering that positive experiences are taken into account as parts of high levels of needs and performance among the caregivers, it seems that improving such positive experiences requires specific and complementary interventions.